Educational Explorations of Chemical Kinetics in a Problem Based Learning Context - D’Ottone, Luca; Ochonogor, Enunuwe Chuckunoye (Orbital: The Electronic Journal of Chemistry, 2017)
The effectiveness of Problem Based learning in the context of chemical education has been tested by using different sets of computer based simulations as teaching aid over a two-year period in a major college of the Southern United States of America. By running simulations of a simple reaction’s system on a JAVA based simulator, students were then able to earn a substantial improvement in their test scores. Students’ improvements, measured with a four-group Solomon test composed of multiple choice questions, were similar or better of the improvements of students that followed the traditional teaching and learning study path. This study underlines the fact that PBL can be effectively used in a college classroom to complement the textbook and to raise awareness amongst students of the time and efforts needed to achieve measurable progresses in a simulated research environment. DOI: http://dx.doi.org/10.17807/orbital.v9i4.1049